Overview of surgical training and assessment of surgical skills: a narrative review - Berg, Margareta; Dahlin, Lars B.; Kjellman, Magnus (Frontiers in Surgery, 2025)
ObjectivesTo assess the existence of international, scientifically validated methods for manual surgical skills training and assessment. The aim was to create a descriptive chronological summary of the existing evidence and conclusions in the included articles.MethodsPubMed and Scopus were searched twice for reviews published between 1997 and October 2023 and between 1997 and January 2024. The search terms used were “review,” “surgical training,” “surgical skills,” “assessment,” and “evaluation” in combinations. In all, 38 reviews were included (systematic and non-systematic). In addition, 30 non-reviews were selected for the introduction and the historical background. Publications on non-technical skills were excluded.ResultsGreat efforts have been invested by committees and working groups to define methods for surgical training and assessment. However, the work was found to be scattered, without attempts to be overarching and internationally valuable, and few training methods were strictly scientifically validated. Many reviews were limited to (1) one surgical procedure, (2) to one surgical specialty, (3) to one surgical method such as endoscopic procedures or “robotics,” or (4) to a limited geographical area.ConclusionsScientifically validated, generally applicable methods for surgical training and assessment could not be found. Further research is needed to find simple, equal, and overarching methods to allow valid and reliable comparisons of manual surgical competencies across borders, in financially strained healthcare where resources for adequate training and evaluation of skills may not be available. Financial aspects can be included in future studies, to correlate costs for training with costs for avoidable surgical complications.